PERSEPSI WISATAWAN TENTANG DAYA TARIK WISATA PEMANDIAN TIRTA ALAMI KABUPATEN PADANG PARIAMAN - Febrina, Nini; Chair, Ira Meirina; Waryono, Waryono (Journal of Home Economics and Tourism, 2015)
The purpose of research is to determine the tourist’s perceptions about thetraction of tourism Pemandian Tirta Alami Kabupaten Padang Pariaman. Thisresearch consists of four indicators are: attraction, accessibilities, amenities, andancillary services. This type of research is descriptive research using surveymethod. Population in this research amounted to 16478 people’s. Samplingtechnique is non probability sampling, using incidental sampling. Sample numberin this research amounted for 100 people’s. Data collection using a questionnairebased on a Likert scale that tested for validity and reliability. Based on the resultsof the study concluded that in general the tourist’s perceptions about the tractionof tourism Pemandian Tirta Alami Kabupaten Padang Pariaman at categorysufficiently with average’s is 173,79 distance of score in 168 – <210 byinterpretation 37%.